"I Suspect That the Pictures Are Stolen": Romance Fraud, Identity Crime, and Responding to Suspicions of Inauthentic Identities. (August 2022) - Cross, Cassandra; Layt, Rebecca
Romance fraud impacts the lives of thousands of people globally. Financial losses exceed millions of dollars each year and are steadily increasing annually. It occurs when an offender uses the guise of an intimate relationship to gain a financial advantage. Offenders use a variety of platforms and communications methods to target victims and develop the required trust and rapport to defraud them. As part of this process, offenders use false identities. This can be through the misappropriation of a genuine person's identity, or it can be through the stealing of photos and other images of a genuine person to create a false or fictitious identity. In this way, romance fraud encompasses two categories of victims: those who lose money through a relationship and those who are subject to identity crime by romance fraud offenders. This article examines how individuals responded to suspicions of inauthentic identities to a person they were communicating with online. It uses romance fraud complaints lodged with Scamwatch (an Australian online fraud porting portal) between July 2018 and July 2019 (inclusive). The qualitative analysis indicates that many complainants used an internet search to verify or refute their suspicions about their partner. This yielded substantiated results in many cases and confirmed that the offender's identity was not genuine. The article explores the implications for this victim-based detection strategy. In doing this, it argues that while effective for romance fraud victims, responses can further exacerbate the ongoing harms experienced by those whose identities have been compromised by romance fraud offenders. The article concludes with a discussion about the future effectiveness of internet searches to reduce romance fraud and the impact of this strategy on third parties whose identities are compromised by offenders.